Peran Sertifikasi Halal dalam Melindungi Konsumen Muslim: Tinjauan Hukum Islam dan Hukum Nasional - Agustin, Adelia Maelani; Destiawan, Firda Shauma; Yulianto, Moch Diki; Gina, Okta Nurul; Indriani, Sulis; Suresman, Edi (Media Hukum Indonesia (MHI), 2025)
Halal certification is an important instrument to ensure the halalness of products which aims to protect the interests of Muslims. The position of halal certification in the Indonesian national legal system is very important because it has been regulated in legislation, especially in Law Number 33 of 2014 concerning Halal Product Guarantee. In addition, the halal fatwa issued by MUI is also respected and followed by the government and the Muslim community. This study aims to analyze the role of halal certification in protecting Muslim consumers based on the perspective of Islamic law and national law. The method used in this research is a literature study with a qualitative descriptive approach to examine the sources of Islamic law and national regulations related to halal certification. The results of the study show that halal certification has a strategic role in providing legal certainty to Muslim consumers and protecting their rights to avoid products that are not in accordance with Sharia. Halal certification is not only a religious obligation but also a form of legal protection for Muslim consumers, so synergy between Islamic law and national law is needed to ensure its effectiveness.